The study of the heating efficiency of the coil-type electric stove with commonly used cooking utensils in boiling water - Bunga, Gerneil J.; Villanueva, Eliseo P. (2000)
A three separate three-factor fixed-effect model experimental design was used to study the heating efficiency of the electric stove in boiling water. Each experimental design used the three levels of water as reference. First level of water is 1000 ml, the second is 2000 ml, and the third is 3000 ml. The three factors were Factor A, Clay Enclosure; Factor B, Stove Setting and Factor C, Water Container. The three volumes of water were also considered to determine the effect on the efficiency of the electric stove. At 95% confidence level, for 1000 ml of water, only Factors B and C were statistically significant but their interactions were not. For 2000 ml and 3000 ml of water, the three factors and the interactions between Factors B and C were statistically significant. The efficiency of the electric stove increases as the volume of water increases. The efficiency was higher when the stove setting was medium. The clay enclosure helped but not quite significantly in reducing the bulk of heat transfer loss
Keywords: Electric stove; Mindanao studies